A new record of plant parasitic green algae, Cephaleuros diffusus (Trentepohliaceae, Chlorophyta), on Acacia auriculiformis hosts in Thailand - ANURAG SUNPAPAO; MUTIARA K PITALOKA (Biodiversitas Journal of Biological Diversity, 2015)
Sunpapao A, Pitaloka MK. 2015. A new record of plant parasitic green algae, Cephaleuros diffusus (Trentepohliaceae, Chlorophyta), on Acacia auriculiformis hosts in Thailand. Biodiversitas 16: 116-120. Cephaleuros diffusus algae were found to cause leaf spot disease of the host Acacia auriculiformis. The identification was based on morphological and molecular properties. The observed morphology identified the algae as C. diffusus. Transverse sections of the host leaves were used to quantify the disease severity of the host in terms of a four-point necrosis index. The host’s lesions were subcuticular and subepidermal on the upper leaf surfaces. The identification of the algae was confirmed from molecular analysis, and a phylogenetic tree distinguished our samples from other Cephaleuros species. This is the first report of C. diffusus on Acacia auriculiformis in Thailand. Key words: Cephaleuros, disease severity, morphology, necrosis, phylogenetic analysis